Pendampingan Keluarga dan Penderita Sumbing Bibir dan Langit-Langit Terhadap Penatalaksanaan Operasi Menggunakan Strategi Social Marketing Volunteer - Ulfa Elfiah; Arif Arif; Kushariyadi Kushariyadi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Mentoring families and people with cleft lip and palate surgery to treatment are still not optimal in Jember city. Due before 2014, there is no hospital that specializes in the treatment of cleft lip and palate social concept, partnering with community empowerment companion. It is also caused by a lack of specific strategies used by the facilitators for this. The existence of a social marketing volunteer strategy, a strategy that has been shown to have positive implications for the handling of cleft lip and palate due to effective direct communication between social worker with sufferers and their families so that patients and families more easily understanding the process of handling lip and palate. This improved can reduce the morbidity and even mortality rates in Jember agroindustry area. In this community service, we engage in activities that consist of 1) the stage of pre-hospitalization, 2) phase of hospitalization and, 3) the stage of post-hospitalization. The purpose of this public service is to apply the strategy social marketing volunteers in order to streamline the handling of cleft lip and palate. Mentoring families and people with cleft lip and palate surgery to treatment using strategy volunteer social marketing are very efficient.